RNA Sequence Profiling Reveals Unique Immune and Metabolic Features of Breast Cancer Brain Metastases - Xiao, Limei; Zhou, Jie; Liu, Hongyi; Zhou, Yuanyuan; Chen, Weibin; Cui, Wugeng; Zhao, Yilin (Frontiers in Oncology, 2021)
There is an urgent need to improve our understanding of breast cancer brain metastases (BCBMs). Thus, we obtained transcriptome data of BCBMs, primary breast cancers (BCs), and extracranial metastases (BCEMs) from the Gene Expression Omnibus (GEO) database, including GSE43837, GSE14017, and GSE14018, for immune and metabolic analysis. Firstly, we performed immune and metabolic analysis on BCBMs and primary breast cancers of GSE43837 using RNA sequence. We identified significant immunosuppression and gene signatures associated with immune infiltration in BCBMs; the lower the expression of the signatures, the worse the prognosis of breast cancer patients in the Kaplan–Meier (KM) plotter [Breast cancer] database. We also identified increased oxidative phosphorylation (OXPHOS) utilization in BCBMs compared with BCs and gene signatures associated with increased OXPHOS utilization in BCBMs; the higher the expression of the signatures, the worse the prognosis of breast cancer patients in the KM plotter [Breast cancer] database, which can predict the prognosis of breast cancer patients better, as it can also predict the prognosis of patients with different breast cancer subtypes. In addition, we performed immune and metabolic analysis on BCBMs and extracranial metastases of GSE14017 and GSE14018 using RNA sequence. Compared with extracranial metastases, we identified more significant immunosuppression but no difference in OXPHOS utilization in BCBMs, which may be because OXPHOS was also involved in extracranial metastases. We have proven that OXPHOS was functionally significant in metastasis in vitro assays. Oligomycin, an OXPHOS inhibitor, substantially attenuated the migration and invasion potential of breast cancer cells. Our study provides new insights into the pathogenesis of BCBMs. Significance Our study reports the most comprehensive gene expression analysis of BCBMs, BCs and extracranial metastases to date. We identified immunosuppression and OXPHOS enrichment in BCBMs compared with BCs, which provide new insights into the pathogenesis of BCBMs and will facilitate the development of new therapeutic strategies for patients with BCBMs.